Anatomy and Physiology of Hamstring Injury - Kumazaki, T.; Ehara, Y.; Sakai, T. (International Journal of Sports Medicine, 2012)
The hamstring muscles were analyzed anatomically and physiologically to clarify the specific reasons for the incidence of muscle strain of the hamstrings. For the anatomical study, hamstring muscles of 13 embalmed cadavers were dissected. For the physiological study, the knee flexor torque and surface electromyographic (EMG) signals were measured during isometric contraction of hamstring muscles in 10 healthy adults. The biceps femoris muscle long head (BF-L) and semimembranosus muscle (SM) had hemi-pennate architecture and their fiber length per total muscle length (FL/TML) was smaller than that of semtendinosus muscle (ST) and biceps femoris muscle short head (BF-S) with other architecture. The decrease of total muscle length per fiber length (ΔTML/FL) was larger in BF-L and SM than in ST and BF-S. The EMG activities at 0° of knee angle were at maximal compared with other knee angles and were of similar level in BF-L, in SM and in ST, whereas they were considerably smaller in BF-S. The EMG at 0° of knee angle activity per physiological cross-sectional area (PCSA) was about 1.6 times greater in BF-L than in SM. These results indicate the highest risk of muscle strain was in BF-L followed by SM.
Keywords: biceps femoris muscle long head; electromyographic (EMG) activity; hamstring muscles; muscle strain